International Journal of Ethiopian Studies (JSTOR)
One of the world's leading scholarly periodicals devoted exclusively to Ethiopia, International Journal of Ethiopian Studies (IJES) is an interdisciplinary, refereed journal dedicated to scholarly research relevant to or informed by the Ethiopian experience. IJES publishes two issues a year of original work in English and/or Amharic to readers around the world.
Keywords: African Studies